PATTERN OF LIPID AND ESSENTIAL FATTY ACID CHANGES IN EARLY DEVELOPMENT OF TIGER GROUPER, Epinephelus fuscoguttatus LARVAE - Muhammad Marzuqi; Ketut Suwirya; Nyoman Adiasmara Giri (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2006)
Development of early stage of larvae depends on body energy content. One of energy source in early larval stage is lipid. Lipid in eggs and early larval development stage of tiger grouper (Epinephelus fuscoguttatus) is used for energy and to maintain permeability of membrane cells. Therefore, lipid class for energy decreases and lipid class for maintaining membrane increases. Lipid quality in larvae depends on the content of essential fatty acid. Lipid from larval stage of neurula; 0, 1, 3, 4, 7, 12, 15, 17, and 20 days after hatching were observed on non polar, polar lipid, and essential fatty acid. The result of experiment showed that proportion of non polar lipid from neurula phase to three days larvae (D3) decreased from 81.9% to 36.5% and polar lipid increased from 18.1% to 63.5%. This result showed, that non polar lipid is used for energy and polar lipid for maintaining membrane of cell body. Essential fatty acid, such as EPA and DHA also decreased in non polar and polar lipid. Decreasing essential fatty acids was higher in non polar lipid than these in polar lipid.